Use of Microfluidic Assays to Develop Reliable and Economic Nucleic Acid Application Technologies, Employing MicroRNAs for the Diagnostic Screening of Colon Cancer in Human Stool in Low-Resource Settings - E. Ahmed Farid; Gouda Mostafa; C. Ahmed Nancy (International Journal of Nutrition, 2020)
Isolation methods that employ readily-available inexpensive supplies on the open market, which are reliable, as well as economical, such as nucleic acid amplification techniques (NAAT) based on microfluidic technology in low-resource research settings (LRRS) that meets the ASSURED guidelines are essential to develop a noninvasive diagnostic colon cancer screen in stool using micro(mi)RNA molecules. A combination of a microfluidic-based MiRNA stool test with a reliable rolling circle amplification/detection method applied to the quantification of miRNA molecules, result in an affordable sensitive and specific isothermal method for the noninvasive quantitative detection of miRNAs in LRRS. Scientists and engineers have become interested in miRNAs, and they have intensified their efforts to apply emerging simple detection tools to the important bioanalytical challenge of quantifying these small 18-26 nt long molecules. Some of the proposed approaches incorporate novel material, such as simple centrifuges and methods based on microfluidic technology, while others utilize the interesting biological properties of these molecules, such as forming branched RCA structures, allowing for the detection of these biomarker molecules at an attomolar
Keywords: colon cancer